Technique of Overlap Extension by Polymerase Chain Reaction for Splicing Cauliflower Mosaic Virus (CaMV) 35S Promoter and DhPEX11-Like - Ikawati, Silvi; Yen, Yung Fu (Graduate School, Universitas Brawijaya, 2015)
The promoter plays an important role in the regulation of gene expression. The problem is some of binary vector that absence from promoter at cloning site. The cauliflower mosaic virus (CaMV) 35S promoter is a strong and constitutive promoter that widely used to produce transgenic organisms. In this experiment the cauliflower mosaic virus (CaMV) 35S promoter was spliced at upstream of DhPEX11-like for driving downstream transgenes DhPEX11-like expression used the technique of Overlap Extension by The Polymerase Chain Reaction. In gene splicing, internal primers are used to amplify some overlapping regions of both genes and then these internal primers are combined with the external primers in PCR process which allows amplification of the entire region. In the experiment, the recombinant PCR successfully spliced the 35S-DhPEX11 gene. This method is simple, rapid and reduced reagents used because it does not need many vector constructions.Keywords: DhPEX11-Like, Gene splicing, Oligonucleotide, PCR, Promoter